Alih Kode dan Campur Kode dalam Film Budi Pekerti 2023 - Aziza Ula Fallahi (Institut Agama Islam Negeri Curup, 2025)
Language becomes a vital communication tool in social interaction of multilingual society like Indonesia, code switching and code mixing phenomena are common, especially in entertainment, including film. Film as a representation of daily life often contains linguistic practices that reflect the social and cultural dynamics of society. The film